Pengaruh Media Sosial sebagai Tempat Curhat terhadap Kesehatan Mental Mahasiswa Stain Madina - Ilpa Hasanah (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2026)
Social media has become an alternative space for emotional expression among university students, particularly as a medium for sharing personal problems or emotional distress. This study aims to examine the effect of social media use as a venting platform on the mental health of students at STAIN Mandailing Natal. A quantitative associative research design was employed, involving 25 fifth-semester students as respondents. Data were collected using a Likert-scale questionnaire measuring the intensity of social media venting behavior and mental health indicators, including stress, anxiety, mood, and self-confidence. The data were analyzed using descriptive statistics and inferential tests, including correlation and simple linear regression. The findings indicate that social media use as a place for venting has a significant relationship with students’ mental health. Positive responses received through social media tend to improve emotional well-being, while negative responses may increase stress and anxiety levels. These findings suggest that social media can function both as a supportive and risky environment for students’ mental health, depending on how it is used. Therefore, students are encouraged to use social media wisely, and educational institutions are advised to provide mental health literacy and guidance related to healthy social media use.